Clinical characteristics and outcome of vasculitides - Paudyal, Buddhi Prasad; Rajbhandari, Anjana Education (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Vasculitides can cause significant morbidity and mortality if not treated on time. There is lack of data locally. This study aims to define the pattern, clinical characteristics, and outcome of vasculitides.Methods: This was a cross sectional study between January 2011 and December 2015 at Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal. The medical records of patients diagnosed with vasculitides in adults rheumatology service of the hospital were reviewed.Results: Ninety six patients were diagnosed with vasculitides during the study period. The mean age was 42.2 years. Sixty nine (71.8%) patient had small vessel, 20 (20.8%) large vessel and five (5.2%) had variable vessel vasculitides. Seventy five patients (78.1%) had primary and 21 (21.8%) secondary vasculitides. Cutaneous leucocytoclasticangitis was seen in 27 (28.1%), Takayasu arteritis in 17 (17.7), Henoch-Schonlein purpura in 11 (11.4%) and Rheumatoid arthritis associated vasculitis in nine patients. Purpura was present in all 96 (100%). The overall mortality was 9 (9.3%).Conclusions: Primary vasculitides were more common than secondary forms. Small vessel vasculitis was the most common. Cutaneous symptoms were predominant features. The mortality was attributed to active disease, sepsis, and complications of the primary disease. Journal of Patan Academy of Health  Sciences. 2016 Dec;3(2):3-9